2004
DOI: 10.1534/genetics.166.2.913
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Breakdown Caused by Substitution of the X Chromosome Between Two Mouse Subspecies

Abstract: Hybrid breakdown is a type of reproductive failure that appears after the F 2 generation of crosses between different species or subspecies. It is caused by incompatibility between interacting genes. Genetic analysis of hybrid breakdown, particularly in higher animals, has been hampered by its complex nature (i.e., it involves more than two genes, and the phenotype is recessive). We studied hybrid breakdown using a new consomic strain, C57BL/6J-X MSM , in which the X chromosome of C57BL/6J (derived mostly from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
134
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(154 citation statements)
references
References 29 publications
(5 reference statements)
16
134
4
Order By: Relevance
“…One possibility is that the replacement occurred as a consequence of random drift, as postulated earlier for the replacement of CAS by MUS mtDNA haplotypes under the 'CAS first' scenario. However, other possibilities are worthy of mention, including more effective long-distance dispersal of male mice across hybrid zones (Hare, 2001;Wen et al, 2004) and the possibility of differential production of abnormal sperm types in inter-subspecies hybrids involving males of CAS vs MUS Y chromosome type (Oka et al, 2004).…”
Section: Who Arrived First -Cas or Mus?mentioning
confidence: 99%
“…One possibility is that the replacement occurred as a consequence of random drift, as postulated earlier for the replacement of CAS by MUS mtDNA haplotypes under the 'CAS first' scenario. However, other possibilities are worthy of mention, including more effective long-distance dispersal of male mice across hybrid zones (Hare, 2001;Wen et al, 2004) and the possibility of differential production of abnormal sperm types in inter-subspecies hybrids involving males of CAS vs MUS Y chromosome type (Oka et al, 2004).…”
Section: Who Arrived First -Cas or Mus?mentioning
confidence: 99%
“…Substantial effort directed toward finding the incompatibilities that underlie hybrid male sterility between M. m. domesticus and M. m. musculus has revealed some genetic patterns. First, the X chromosome is an important contributor (Oka et al 2004;Storchová et al 2004;Britton-Davidian et al 2005;Good et al 2008aGood et al ,b, 2010Vyskočilová et al 2009). F 1 's from most crosses follow Haldane's rule (Haldane 1922), with hybrid females showing few signs of sterility.…”
mentioning
confidence: 99%
“…Genetic studies in Drosophila demonstrated an excess of hybrid sterility loci on the X chromosome, a phenomenon referred to as Flarge X-effect_ (Orr & Coyne 1989, Tao et al 2003. Several X-linked hybrid sterility loci were also reported in mice (Oka et al 2004, Storchova et al 2004. These genetic studies suggest that hybrid sterility might be caused by incompatibility of multiple loci (or genes).…”
Section: Implications Of X-linked Meiosis Factorsmentioning
confidence: 99%